SUSTAINABILITY REPORTING AND FINANCIAL PERFORMANCE OF COMMERCIAL BANKS IN KENYA - Muthaura, Timothy (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
This concept paper explores the relationship between sustainability reporting and the financial performance of commercial banks in Kenya. It aims to provide an overview of existing literature, identify research gaps, and propose a framework for further investigation. The paper highlights the growing importance of ESG considerations in the banking sector, outlines potential mechanisms through which ESG factors can influence financial performance, and suggests avenues for future research.